A heart lost in wonder the life and faith of Gerard Manley Hopkins - Randall, Catharine 1957- (Library of religious biography, 2020)
Gerard Manley Hopkins, one of the most beloved English-language poets of all time, lived a life charged with religious drama and vision. The product of a High-Church Anglican family, Hopkins eventually converted to Roman Catholicism and became a priest--after which he stopped writing poetry for many years and became completely estranged from his Protestant family. A Heart Lost in Wonder provides perspective on the life and work of Gerard Manley Hopkins through both religious and literary interpretation. Catharine Randall tells the story of Hopkins's intense, charged, and troubled life, and along the way shows readers the riches of religious insight he packed into his poetry. By exploring the poet's inner life and the Victorian world in which he lived, Randall helps readers to understand better the context and vision of his astonishing and enduring work